Decay of anti-Bordetella pertussis antibodies in women of childbearing age following COVID-19 non-pharmaceutical measures. Issue 27 (15th June 2022) - Reicherz, Frederic; Golding, Liam; Lavoie, Pascal M.; Abu-Raya, Bahaa
Abstract: Background: Immunization against Bordetella pertussis during pregnancy reduces morbidity from severe pertussis in young infants via trans -placental transfer of anti- B. pertussis Immunoglobulin G (IgG). Studies have reported a near disappearance of respiratory pathogens including B. pertussis following implementation of mitigation strategies to control Coronavirus disease 2019 (COVID-19). We explored how immunity against B. pertussis changed in women of childbearing-age through the COVID-19 pandemic. Methods: Paired blood samples from females of childbearing-age collected at the beginning (May-June 2020) and nearly one year into the COVID-19 pandemic (February-May 2021) in British Columbia (BC), Canada were tested for anti- B. pertussis IgG levels. To ascertain whether early-pandemic IgG levels in 2020 reflected levels in pregnant women early in gestation, 1st trimester sera collected from age-matched healthy pregnant women in 2018 and 2019 were tested for anti- B. pertussis IgG. Levels were compared by t tests. P-value of 0.05 was assigned and statistical significance was set as p < 0.016 using Bonferroni correction. Results: Annual provincial B. pertussis incidences per 100, 000 in BC in 2020 (3/100, 000) and 2021 (<1/100, 000) approximated the lowest levels since 1990. In 2021 vs. 2020, anti-pertussis toxin (PT), filamentous hemagglutinin (FHA) and pertactin (PRN) IgG levels declined in women of childbearing-age: 6.8 IU/ml (95 %CI, 4.2–10.9) vs. 8.4 IU/ml (5.1–13.9; p = 0.004); 18.8 IU/ml (10.9–32.2) vs. 23.6 IU/ml (13.2–42.1; p < 0.001); and 37.1 IU/ml (18.1–75.9) vs. 47.2 IU/ml (24.8–89.9; p = 0.092), respectively. Although all values were slightly higher, anti-PT, FHA and PRN IgG levels in women of childbearing age did not significantly differ in 2020 compared with early-gestation pregnant women in 2018–2019, 8.4 IU/ml (95% CI, 5.1–13.9) vs. 5.4 IU/ml (95% CI, 3.8–7.7; p = 0.166), 23.6 IU/ml (95% CI, 13.2–42.1) vs. 20.1 IU/ml (95% CI, 13.4–30.2; p = 0.656), and 47.2 IU/ml (24.8–89.9) vs. 17.3 IU/ml (95% CI, 10.5–28.7; p = 0.021), respectively. Discussion: B. pertussis infections should be closely monitored during the relaxing of mitigation measures for COVID-19.